Identifikasi Senyawa Metabolit Sekunder pada Durian (Durio zibethinus Murr) - Aji Suteja; Emmy Harso Kardhinata; Rosliana Lubis (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2019)
This study aims to determine how to identify the types of secondary metabolite compounds contained in durian leaves. The study was conducted by an experimental method by identifying secondary metabolite compounds on durian leaves using phytochemical screening. The sample criteria used were the leaf buds and all the leaf strands (except the leaf bones). The results of the study showed that of the three types of durian leaves namely copper, baskets and Sp A. There are several types of secondary metabolite compounds including alkaloids, steroids, and terpenoids. Phytochemical screening analysis was carried out using thin layer chromatography by showing RF values on three types of durian leaves using methanol and ethyl acetate solvents in a ratio of 3: 1. RF value on copper durian is 0.97, bakul durian is 0.95 and Sp durian. A 0.94.